Protein Adsorption From Biofluids on Silica Nanoparticles: Corona Analysis as a Function of Particle Diameter and Porosity - Clemments, Alden M. (ACS Appl Mater Interfaces, 2015)
A study on the adsorption of proteins from fetal bovine serum (FBS) on spherical dense and mesoporous silica nanoparticles with a wide range of diameters, from 70 to 900 nm, is presented. Monodisperse populations of particles with a range of diameters were obtained through modifications of the Stöber method. Extensive characterization of the particles was then performed using N(2) physisorption, TEM, DLS, and ζ-potential. Following serum exposure, proteomic evaluation in concert with thermogravimetric analysis revealed the associated concentrations of each protein identified in the hard corona. Small particles adsorbed the largest amount of protein, due to their larger external surface area. Proteins with low molecular weights (<50 kDa) composed the majority of the protein corona, totaling between 60 and 80 % of the total mass of adsorbed protein. Here, the higher surface curvature of small particles favors the enrichment of smaller proteins. Porosity does not promote protein adsorption, but improves deposition of the low molecular weight protein fraction due to the size exclusion effect related to pore diameter. These results have important implications for the use of dense and porous silica nanoparticles in biomedical applications.